Pengaruh Corporate Social Responsibility Terhadap Willingness To Purchase dengan Brand Image Sebagai Variabel Mediasi (Studi pada Kampung Dongeng Teh Sisri) - Helen Helen; Hetty Karunia Tunjungsari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to obtain an analysis of marketing initiatives through corporate social responsibility to increase willingness to purchase that gives effect through brand image. Especially for brands that are experiencing a brand image crisis, through this research, one of the steps that can be taken is through corporate social responsibility. The research sample uses a questionnaire method consisting of 230 respondents in two elementary schools that were held in the Kampung Dongeng Teh Sisri Village. Hypothesis testing uses multiple linear regression statistical methods. The results showed that corporate social responsibility had a positive effect on willingness to purchase both directly and through brand image, corporate social responsibility had a positive effect on brand image, then brand image also had a positive effect on willingness to purchase.